Failure Characteristics and Stability Control of Bolt Support in Thick-Coal-Seam Roadway of Three Typical Coal Mines in China - Zhe Xiang; Nong Zhang; Deyu Qian; Zhengzheng Xie; Chenghao Zhang; Feng Guo; Sujian Wang (Shock and Vibration)
Roadways in thick coal seams are widely distributed in China. However, due to the relatively developed cracks and brittleness of coal, the support failure of thick-coal-seam roadways frequently occurs. Therefore, the study of bolt failure characteristics and new anchoring technology is very important for the safety control of thick-coal-seam roadways. Based on field observations, the failure mechanism of selected roadway failures under distinct conditions at three representative coal mines in eastern and western China was analyzed. Recommendations are provided for roadway safety control. The results show that the strength and dimension of the anchoring structure in the coal roof of thick-coal-seam roadways are the decisive factors for the resistance of the roadway convergence and stress disturbance. The thick anchoring structure in the roof constructed by flexible long bolts can effectively solve the problem of support failure caused by insufficient support length of traditional rebar bolts under the condition of extra-thick coal roof and thick coal roof with weak interlayers. The concepts and techniques presented in the paper provide a reference for the design of roadway support under similar geological conditions and dynamic load.